2005
DOI: 10.1080/10253890500456287
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced involvement of brain vasopressin V1 receptors in cardiovascular responses to stress in rats with myocardial infarction

Abstract: Stress is one of the factors provoking cardiovascular complications. The purpose of the study was to explore the role of vasopressin (VP) in central control of arterial blood pressure and heart rate under resting conditions and during stimulation by an alarming stress (air jet stress) in myocardial infarct-induced cardiac failure. Six groups of male Sprague Dawley (SD) rats were subjected either to sham surgery (sham rats) or to ligation of a left coronary artery (infarcted rats). After 5 weeks both infarcted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 46 publications
7
48
0
Order By: Relevance
“…administration of an AT1 or V1a antagonist (Cudnoch-Jedrzejewska et al 2007;Dobruch et al 2005;Zhang et al 1999). Accordingly, it was concluded that myocardial infarction results in an enhanced activation of those central AT1 and V1a receptors which participate in cardiovascular regulation under resting conditions and during stress (Cudnoch-Jedrzejewska et al 2007;Dobruch et al 2005;Zhang et al 1999). In our previous studies, we described sensitisation to the central pressor action of VP, and an interaction between AT1 and V1a receptors in central cardiovascular control in infarcted rats (Cudnoch-Jedrzejewska et al 2007;Dobruch et al 2005).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…administration of an AT1 or V1a antagonist (Cudnoch-Jedrzejewska et al 2007;Dobruch et al 2005;Zhang et al 1999). Accordingly, it was concluded that myocardial infarction results in an enhanced activation of those central AT1 and V1a receptors which participate in cardiovascular regulation under resting conditions and during stress (Cudnoch-Jedrzejewska et al 2007;Dobruch et al 2005;Zhang et al 1999). In our previous studies, we described sensitisation to the central pressor action of VP, and an interaction between AT1 and V1a receptors in central cardiovascular control in infarcted rats (Cudnoch-Jedrzejewska et al 2007;Dobruch et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…The infarct size was determined by planimetry as described by Leenen et al (1999), with some minor modifications , and expressed as a percentage of the total left ventricle surface. In addition, the heart was examined histologically to confirm the presence of an infarct scar according to the procedure described previously (Cudnoch-Jędrzejewska et al 2005;Dobruch et al 2005). To verify whether the i.c.v.…”
Section: Post-mortem Examinationmentioning
confidence: 99%
See 3 more Smart Citations